How do SMA-linked mutations of SMN1 lead to structural/functional deficiency of the SMA protein? - Wei Li (PLoS ONE, 2017)
Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease with dysfunctional α-motor neurons in the anterior horn of the spinal cord. SMA is caused by loss (∼95% of SMA cases) or mutation (∼5% of SMA cases) of the survival motor neuron 1 gene SMN1. As the product of SMN1, SMN is a component of the SMN complex, and is also involved in the biosynthesis of the small nuclear ribonucleoproteins (snRNPs), which play critical roles in pre-mRNA splicing in the pathogenesis of SMA. To investigate how SMA-linked mutations of SMN1 lead to structural/functional deficiency of SMN, a set of computational analysis of SMN-related structures were conducted and are described in this article. Of extraordinary interest, the structural analysis highlights three SMN residues (Asp44, Glu134 and Gln136) with SMA-linked missense mutations, which cause disruptions of electrostatic interactions for Asp44, Glu134 and Gln136, and result in three functionally deficient SMA-linked SMN mutants, Asp44Val, Glu134Lys and Gln136Glu. From the computational analysis, it is also possible that SMN's Lys45 and Asp36 act as two electrostatic clips at the SMN-Gemin2 complex structure interface.